Figure 4 in New contributions to the marine benthic ciliates from the Antarctic area, including description of seven new species (Protozoa, Ciliophora) - Wilbert, Norbert; Song, Weibo (Zenodo, 2005)
Figure 4. Pithites pelagicus nov. spec. from life (A–D) and protargol impregnation (E–J). (A) ventral view of a typical specimen, arrowhead marks the contractile vacuole, arrow indicates the subcaudal cavity; (B) lateral view, arrow indicates the cytostome, arrowhead marks the subcaudal cavity; (C) pattern of movement; (D) lateral view, to show the body shape; (E) left lateral view, to show the orientation of the cytopharynx (arrow); (F) apical view, arrow points to the terminal kinety (''dorsal brush''); (G) ventral view, to show the general infraciliature, arrowheads mark the densely ciliated part of left kineties, arrow points to pore of contractile vacuole, while the double-arrowheads mark the subcaudal cavity; (H) dorsal view, arrow marks the terminal kinety; (I, J) ventral view of cells in division, arrow in I marks the newly forming buccal apparatus, while in J it indicates the densely ciliated portion of kineties. Scale bars: 35 Mm (A, D, E); 30 Mm (G). : Published as part of Wilbert, Norbert & Song, Weibo, 2005, New contributions to the marine benthic ciliates from the Antarctic area, including description of seven new species (Protozoa, Ciliophora), pp. 935-973 in Journal of Natural History 39 (13) on page 945, DOI: 10.1080/00222930400001509, http://zenodo.org/record/4657793